Assessment of knowledge and practices of ASHA workers related to maternal-child health and their performance affecting factors: a mixed method study in Deganga block, North 24 parganas district, West Bengal, India - Pal, Jayita; Roy, Suvendu; Nandi, Swagata; Satapathy, Sankalpa (International Journal of Research in Medical Sciences, 2019)
Background: ASHA acts as a ‘bridge’ between the rural people and health service outlets and plays a central role in achieving national health and population policy goal. ASHAs form the backbone of the NRHM. They need to provide preventive, promotive and curative health facilities in the rural community. Maternal and child health is an important public health issue which indicates level of socio-economic development in each and every country. ASHA workers are the main front-line workers in primary health care delivery system who are expected to work in this domain to bring out betterment in RCH indicators. Method: It was a mixed method study. Quantitative portion was descriptive, cross-sectional and qualitative part was focus group discussion (FGD). The study had been conducted in one block (Deganga block) of North 24 parganas district of West Bengal which was previous to selected purposively for the study. All ASHAs of Deganga block and one beneficiary mother (mother who had a baby of less than 1 year) for each ASHA from her area of work had been included as study population. ASHA- Beneficiary dyad had been interviewed with a predesigned pretested questionnaire after taking informed consent. Result: More than half of the study population (64.7% and 50.5 %) had overall good knowledge and practice score related to maternal-child health and family planning respectively, though they had poor knowledge in updated dosage schedule of iron folic acid tablets, proper attachment techniques for successful breast feeding, missed doses of OCP, ECP, IUCD and safe period. They performed less efficiently in areas like counselling about harmful effects of addiction during pregnancy, birth preparedness and complication readiness, colostrum feeding, weaning, ECP and MTP. Mainly inadequate remuneration and lack of job satisfaction were the factors hindering their performance. Conclusion: Frequent refresher courses, regular monitoring and supportive supervisions by respective higher authority, administrative steps for combating their dissatisfaction are of utmost importance to improve their performance.